تأثير ردميات من الرمل خلف و أسفل الجدران الاستنادية على استقرارها - توفيق فياض (Tishreen University, 2018)
The use of retaining walls is widely used in Syria, as a foundation for soil erosion and preventing it from collapsing. For the ease of implementation of these facilities and provide the necessary means to implement them (building materials - local expertise - Covraj ...). As far as implementation is easy, care must be taken to study and implement this type of facility. Start from studying their safety factors (safety on slide - safety on the coup - endurance of the soil under these installations ...)   In this article, a soil study was conducted in which the soil of the site was destroyed due to a change in the weather conditions at the site, which led to a collapse in the soil and the disruption of the implementation of the installations in the site such as buildings and others. The soil of the site was studied and the physical and mechanical characteristics of the site were determined. And the extent to which the retaining wall can be implemented at the site. With the determination of safety factors for this site, and then the effect of the use of sand dunes (study of a type of sand) on the safety factors of this wall. And the purpose of all this is to show the role of these sand dunes in the stability of the retaining walls, and to reduce the dimensions of these walls and its money from a reflection on the economic and safety of these installations. Samples of different soil species were brought to the laboratories of the Faculty of Civil Engineering at Tishreen University and laboratory experiments were carried out and the results of the experiments were evaluated.   ينتشر استخدام الجدران الاستنادية بشكل واسع في سوريا، كمنشآت لسند التربة و منعها من الانهيار. و ذلك لسهولة تنفيذ هذه المنشآت و توفر الإمكانيات اللازمة لتنفيذها (مواد بناء - خبرات محلية - كوفراج...). و بقدر سهولة التنفيذ يجب العناية بدراسة و تنفيذ هذا النوع من المنشآت. بدءً من دراسة عوامل الأمان الخاصة بها (الأمان على الانزلاق - الأمان على الانقلاب-قدرة التحمل التربة تحت هذه المنشآت...).   تمت في هذه المقالة دراسة تربة موقع حصل فيه انهيار لتربة الموقع نتيجة تغير للعوامل الجوية في الموقع مما أدى لانهيار في التربة و تعطيل تنفيذ المنشآت في الموقع كالأبنية و غيرها. تمت دراسة تربة الموقع و تحديد المواصفات الفيزيائية و الميكانيكية للترب. ومدى إمكانية تنفيذ جدار استنادي في الموقع. مع تحديد عوامل الأمان لهذا الجدار، ومن ثم تأثير استخدام ردميات من الرمل (دراسة نوع من أنواع الرمل) على عوامل الأمان لهذا الجدار. و الغاية من ذلك كله تبيان دور هذه الردميات الرملية في استقرار الجدران الاستنادية، و تخفيف أبعاد هذه الجدران و ماله من انعكاس على اقتصادية و أمان هذه المنشآت. تم إحضار عينات من أنواع الترب المختلفة إلى مخابر كلية الهندسة المدنية في جامعة تشرين و إجراء التجارب المخبرية اللازمة عليها و تقييم نتائج التجارب.